Strengthening The Capacity Of Sleman Regency In Protecting The Prambanan Temple Site From Mount Merapi Eruption - Arie Prabowo; Kusuma Kusuma; Bambang Wahyudi; Wilopo Wilopo (International Journal of Education, Vocational and Social Science, 2026)
Mount Merapi is one of the most active volcanoes in Indonesia, administratively located in the southern part of Sleman Regency. Prambanan Temple is a historical site in Sleman Regency that was affected by the eruption of Mount Merapi. To reduce the impact of the eruption of Mount Merapi on the world historical site of Prambanan Temple, capacity building and cooperation from stakeholders in Sleman Regency are needed. The purpose of this study is to analyze the implementation of capacity building in Sleman Regency in protecting the world historical site of Prambanan Temple from the eruption of Mount Merapi. This research method uses a qualitative approach with the research locus carried out in the Sleman Regency area. Data collection techniques through interviews, observation and documentation. The data examination is carried out with triangulation and data analysis techniques using an interactive analysis model. The results of the study show that mitigation focuses on structural aspects, especially post-disaster activities with tarpaulin coverings, while non-structural efforts are not optimal due to gaps in coordination, communication and cooperation between agencies. The Mount Merapi disaster risk assessment in strengthening the capacity of Sleman Regency through strategic efforts ranging from procedures or SOPs to scenarios and alternatives that have been well prepared such as several signs and evacuation symbols. Sleman Regency has implemented innovation and knowledge through its sister village program to provide evacuation information through a mutual cooperation system. Keywords: Mount Merapi, Prambanan Temple, Risk, Institutional Capacity